FRI0016 Inhibition of chronic pain by il4-10 synerkine is superior to IL-4 or IL-10 monotherapy: a novel strategy to restrain (inflammatory) pain in rheumatic diseases. (23rd January 2014) - Eijkelkamp, N.; Hartgring, S. A.; Steen-Louws, C.; Willemen, H.; Mao-Ying, Q.-L.; Heijnen, C.; Hack, E.; Kavelaars, A.; Van Roon, J. A.
Abstract : Background: Chronic pain is a major problem in many diseases, including RA and OA, arising from inflammation or structural damage. It is often associated with glial cell-mediated inflammatory responses in the spinal cord leading to enhanced pain perception (hyperalgesia), which is difficult to treat. Moreover, therapeutic options are limited. Despite the potential of IL4 and IL10 to inhibit inflammation and pain in experimental models, clinical studies were disappointing, likely due to poor bioavailability. We developed a novel option to inhibit multiple inflammatory responses by constructing an IL4/IL10 fusion protein (IL4-10 synerkine). This synerkine is a novel biologic that combines the distinct characteristics of IL4 and IL10, with an increased mass and anticipated improved bioavailability. Strong anti-inflammatory potential of the synerkine was demonstrated in human in vitro assays. Objectives: To investigate the capacity of IL4-10 synerkine to treat chronic pain induced by inflammation or nerve damage. Methods: IL4-10 synerkine, injected intrathecally (it), was tested in 3 mouse models of chronic pain. First, chronic inflammatory hyperalgesia was induced by intraplantar injection of carrageenan. Secondly, we used mice with a cell-specific reduction of ~50% in GRK2 level in microglia/macrophages (LysM-GRK2+/- mice) that develop persistent inflammatory hyperalgesia after a single intraplantar injection of IL-1b, while WT mice develop a transient hyperalgesia. Thirdly, chronic neuropathic pain was induced by spared nerve injury (SNI). Hyperalgesia was assessed by Hargreaves test to determine heat withdrawal latencies and Von Frey hairs to determine mechanical thresholds. To demonstrate surplus value of the synerkine, IL-4 and IL-10 mono and combination therapies were tested. Results: Intraplantar injection of carrageen induced profound persistent hyperalgesia in WT mice. A single it. injection of IL4-10 synerkine completely inhibited established carrageenan-induced persistent hyperalgesia (for 40, 100 and 200 ng all p<0.001) for at least 2 days. The highest dose of IL4-10 synerkine significantly inhibited hyperalgesia for 4 days (p<0.05). Injection of IL4, IL10, or a combination (100 ng) only modestly inhibited hyperalgesia (30-40%) for 1 day. It. administration of IL4-10 synerkine also dose-dependently inhibited IL-1β-induced persistent hyperalgesia in LYSM-GRK2+/- mice. Single injections of 100 ng and higher, completely prevented the development of IL-1β-induced hyperalgesia in LYSM-GRK2+/- mice (p<0.001). Moreover, it shortened the duration of transient IL-1β-induced hyperalgesia in WT mice. Interestingly, IL4-10 synerkine also inhibited mechanical hypersensitivity in the SNI neuropathic pain model, although for shorter time periods (6 hours). Conclusions: IL4-10 synerkine, next to its strong anti-inflammatory properties, also robustly relieves hyperalgesia in models for inflammatory and neuropathic pain, superior to IL4 or IL10 mono or combination therapy. These data underscore the potential of IL4-10 synerkine to inhibit immunopathology and pain in inflammatory and degenerative rheumatic diseases. Disclosure of Interest: None Declared